Battling with infodemic and disinfodemic: the quandary of journalists to report on COVID-19 pandemic in Pakistan. Issue 3 (1st October 2020) - Jamil, Sadia; Appiah-Adjei, Gifty
Abstract : The outbreak of COVID-19 pandemic has impacted all sectors of life. Despite economic downturn, one major impact of global pandemic is the rise of 'infodemic' and 'disinfodemic', which actually creates challenge for the public to access reliable information when they require it. News media plays a crucial role in such stressful situations by providing timely and accurate information about the pandemic. Nevertheless, when the news verification and gatekeeping is weak, dissemination of false information within the infodemic can result in the toxic disinfodemic of disinformation and misinformation. It is imperative to recognize that journalists, especially in restrained environments (like Pakistan), can combat infodemic and disinfodemic about the pandemic when their safety and accessibility to needed information are guaranteed, and when they are not prone to diverse challenges. Therefore, drawing on Reese's hierarchy of influences model, this study seeks to explore the various levels of influences that impact on the Pakistani journalists' reporting and their ability to deal with the challenges of infodemic and disinfodemic amid COVID-19 pandemic. Moreover, this study uses qualitative method of in-depth interviews (online) and employs thematic analysis to address the study's findings.